Peer-Correction Technique in Writing Class - Dezas Perdani, Yella (LPPM Universitas Pancasakti Tegal, 2020)
This study investigated the effectiveness of the peer-correction technique in writing classes. The participants of the study were the students of a Composition 1 Class in one of the universities in Bandung. There were 8 weeks in the process. The peer-correction was done every week with different kinds of paragraphs. For the first week, the students did peer-correction in pairs. It was to know the rules, what to be corrected and how it had to be done. And for the rest of the weeks, they did peer-correction using a laptop and presented the paragraph through an LCD projector so that each of the students got all the attention in class and also could correct their classmates’ paragraphs together. Data collection methods were questionnaires and interviews. There are 22 statements in the questionnaire sheet and 8 questions in the interview session. The results of the research were; there were 5 advantages of applying the pre-correction technique and 2 disadvantages found.